PENGARUH PERSEPSI PEMILIK DAN PENGETAHUAN AKUNTANSI PELAKU USAHA MIKRO KECIL DAN MENENGAH TERHADAP PENGGUNAAN INFORMASI AKUNTANSI (Studi Kasus Pada UMKM Jagung Goreng Air Panas Semurup) - Tiara Lilis Surya (LPPM - STIE SAKTI ALAM KERINCI, 2022)
This study aims to provide empirical evidence regarding the perception and accounting knowledge of business owners in the use of accounting information by testing each variable. Through this research, it can be seen how the perception and accounting knowledge of MSME owners are. The object of research is the Fried Corn UMKM in Semurup Hot Water Village, this UMKM was chosen because this fried corn business is a home business which is a business that is characteristic of the Semurup Hot Air Village community. The analytical model used in this study is a multiple linear regression analysis model which was carried out with the help of the SPSS version 20 computer program for windows. The independent variable in this study is the use of accounting information, while the dependent variable is the perception and knowledge of accounting. The type of data used is primary data. The results of this study prove that there is no effect of perception on the use of accounting information, and there is an effect of accounting knowledge on the use of accounting information.